The C programming language - Kernighan, Brian W. 4 0 16; 1941- Ritchie, Dennis M.; 5 Bell Telephone Laboratories (Upper Saddle River, NJ : Prentice Hall of India, 1988)
A guide to programming computers using the C language that includes a reference manual, exercises designed to help students understand the language, and complete examples.
AT&T Bell Laboratories.;Includes index.
Adult;Adult.
Keywords: 2 -- 0; 6; C (Computer program language). -- 20; 20; 2